PERAN BAHASA DAERAH DALAM PEWARTAAN IMAN KRISTIANI DI FLORES: KAJIAN HISTORIS ATAS KARYA MISIONARIS DI LEMBATA - Harjon, Losianus; Ware Mere, Henok Albert; Yanto Nahak, Antonius Redi; Juang, Afrianus; Hibur, Basilius Indrawahyu; Lando, Kristianus Raja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The history of Christian evangelization in Flores, particularly in Lembata and Solor, reveals that local languages play a crucial role as tools of communication and faith inculturation. Early missionaries recognized that using indigenous languages was essential for making the Gospel understandable and acceptable to communities with existing belief systems and religious traditions. Through local languages, the message of faith was not only conveyed informatively but also connected deeply with the cultural context and lived experiences of the people. This study aims to examine the role of local languages in early missionary work and their relevance in contemporary Church life. It employs a qualitative method with a literature review and historical analysis approach. The findings show that local languages function as cultural identity markers, means of social interaction, and media for religious experience. Language serves not merely as a communication tool but also as a bridge linking humans to their faith experiences and relationship with God. Therefore, preserving local languages in Church practices such as prayer, catechesis, and liturgy is essential to strengthen the faith identity of believers amid the challenges of modernization.